Manajemen Konflik Dalam Meningkatkan Kuantitas Peserta Didik MIS Thoriqil Huda Juwet Ngronggot Nganjuk - Arifin, Bustanul; Hakim, Faisol (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Conflict in the school environment is an inevitable phenomenon, often arising from issues of communication, personal relationships or organizational structure. Effective conflict management can create an environment conducive to learning and have a positive impact on the quantity of learners. This study aims to examine conflict management at MIS Thoriqil Huda Juwet Nganjuk in the context of increasing learner quantity. Using a qualitative approach with a multicase study design, data were collected through in-depth interviews, participatory observation, and documentation. Data sources included the academic community as primary data and related documents and photos as secondary data. Data analysis was conducted through the Miles Huberman model, with the stages of data reduction, data presentation, and conclusion drawing, as well as cross-case analysis for comparison of findings. The results showed that both institutions, MIS Thoriqil Huda Juwet Nganjuk and MTs Darul Ihsan Nganjuk, succeeded in identifying the symptoms and causes of conflict and the parties involved. The comprehensive approach at MTs Darul Ihsan, which involves the boarding school caregiver in conflict resolution, as well as evaluation through incidental supervision, has proven effective in improving the quality of teacher performance. Both institutions showed an improvement in the conducive learning environment, which has the potential to increase the number of students and the overall quality of education.